2007
DOI: 10.1021/bi701202w
|View full text |Cite
|
Sign up to set email alerts
|

α and β Chains of Hemoglobin Inhibit Production of Staphylococcus aureus Exotoxins

Abstract: Prior studies suggest Staphylococcus aureus exotoxins are not produced when the organism is cultured in human blood. Human blood was fractionated into plasma and water-lysed red blood cells and demonstrated that mixtures of α and β globins of hemoglobin (as low as 1 ug/ml) inhibited S. aureus exotoxin production while increasing production of protein A and not affecting bacterial growth. Pepsin but not trypsin digestion destroyed the ability of α and β globin to inhibit exotoxin production. Exotoxin production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 36 publications
(62 reference statements)
4
59
0
Order By: Relevance
“…These conditions include growth in complex media containing animal protein with low glucose (glucose functions as a catabolite repressor of exotoxin production), neutral pH (as expected vaginally during menstruation), temperature of 37°C to 40°C, and oxygen balanced with CO 2 (84,168). As noted previously, blood components, and more specifically hemoglobin peptides, negatively affect production of TSST-1 (147). The introduction of oxygen into the human vagina, a typically anaerobic environment, by tampons is now considered the major reason for the tampon association with mTSS (84,168,169).…”
Section: Staphylococcal Menstrual Tssmentioning
confidence: 90%
See 1 more Smart Citation
“…These conditions include growth in complex media containing animal protein with low glucose (glucose functions as a catabolite repressor of exotoxin production), neutral pH (as expected vaginally during menstruation), temperature of 37°C to 40°C, and oxygen balanced with CO 2 (84,168). As noted previously, blood components, and more specifically hemoglobin peptides, negatively affect production of TSST-1 (147). The introduction of oxygen into the human vagina, a typically anaerobic environment, by tampons is now considered the major reason for the tampon association with mTSS (84,168,169).…”
Section: Staphylococcal Menstrual Tssmentioning
confidence: 90%
“…Investigators have shown that certain superantigens, notably SEA, TSST-1, and SEC, are overrepresented in sepsis cases compared to nonsepsis cases (253)(254)(255). However, it is unlikely that superantigens are directly produced in the bloodstream of patients, since hemoglobin peptides inhibit superantigen production (147). It is more likely that superantigens are produced in focal sites of infection protected from hemoglobin peptides and then secreted into the bloodstream.…”
Section: Staphylococcal Sepsis and Superantigensmentioning
confidence: 99%
“…The environmental triggers and molecular mechanisms that control the production of TSST-1 are complex and not fully understood. Multiple factors, such as glucose, pH, CO 2 , O 2 , NaCl, magnesium concentration, the ␣ and ␤ chains of hemoglobin, and TSST-1 itself, have been assessed and shown to affect toxin production (4,19,46,48,56,59).…”
mentioning
confidence: 99%
“…S. aureus CFU/ml were determined by plate counts from each section. The amount of TSST-1 (g/section) was determined by semiquantitative Western immunoblot analysis, which allows for the detection of TSST-1 in the presence of antibodies and blood components (26). The Western immunoblots were developed with alkaline phosphatase-conjugated antibodies and substrate (3).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies demonstrate that O 2 and CO 2 , iron, pH, glucose, and temperature are factors that can alter the concentration of TSST-1 produced by S. aureus (10,12,25,33,36). Recent in vitro studies have shown that both ␣-and ␤-globin chains of human hemoglobin can inhibit the production of TSST-1 without impacting growth of the organism (26). Given that menstrual blood is rich in hemoglobin, the study suggests that toxigenic S. aureus present on tampons might produce TSST-1 only in areas that lack menstrual blood.…”
mentioning
confidence: 92%